The Effectiveness Biscuits In Increasing Hemoglobin Levels In Pregnant Women - Emanuela Natalia Nua; Regina Ona Adesta; Rosania E.B. Conterius (Universitas Padjadjaran, 2021)
Anemia of pregnancy is still a significant health problem in Indonesia. Various efforts have been made to overcome this problem. Moringa biscuits (Bikelor) processed from Moringa leaves with high iron content are an alternative to increasing hemoglobin levels in pregnant women with anemia. The purpose of this research is to analyze the effectiveness of giving Bikelor to increase Hb in pregnant women with anemia. This research was approved by the health research ethics committee of the Faculty of Medicine, Nusa Cendana University, Kupang. The study used the One Group Pre Test and Post Test Design, conducted from May to October 2020 in the working area of the Waigete and Beru Public Health Centers in Sikka Regency on 20 pregnant women. The research was conducted through 4 stages, namely the stage of making Bikelor, the location of organoleptic testing (testability) for pregnant women to Bikelor, testing of nutrient content, and intervention. The intervention phase was carried out for 14 days in October 2020. The intervention data were analyzed using paired t-test analysis to see the difference in Hb levels before and after giving Bikelor. The results of the study showed that there was a significant difference in the Hb levels of pregnant women before and after being given Bikelor with a p-value of 0.000 (α<0.05). Changes in Hb levels before and after giving Bikelor were 0.8-1.4gr/dl. It showed that Bikelor was one of the food products that can effectively increase Hb levels in pregnant women with anemia. Consumption of Bikelor can increase the Hb level of pregnant women. Pregnant women were expected to continue to consume the iron tablets given or can replace them by consuming Bikelor as a daily snack as much as 4-5 pieces per day